Tafsir Kontemporer dan Hermeneutika Al-Qur’an: Memahami Teks Suci Al-Qur-an Dalam Konteks Kontemporer - Umar Al Faruq; Khoiru Turmudzi; Kartika Maulida; Salman Abdullah (CV. ITTC INDONESIA, 2024)
This article discusses the importance of Qur'ānic hermeneutics as a relevant method of interpretation in the understanding of sacred texts for Muslims. From the introduction to the conclusion, the article highlights the contribution of hermeneutics in broadening the horizons and understanding of the Qur'ān. Hermeneutics is seen as an approach that enables a deep understanding of the sacred text through a process of interpretation that involves the subject and object in a communicative relationship. Hermeneutic figures, both from the West and the Islamic world, have made important contributions to the development of methods of Qur'ānic interpretation, emphasizing the importance of understanding the text from the author's point of view as well as its historical context. In addition, cross-cultural and age-appropriate understanding is also an integral part of Qur'ānic hermeneutics, where cross-cultural and age-appropriate communication is key to broadening insights and understanding of the sacred text. In the context of Islamic religious education, hermeneutics has become an important course in the curriculum structure of the Tafsir and Hadith Science study programs at State Islamic Religious Universities, showing the relevance and need for a deep understanding of the Qur'anic interpretation method. Thus, through the hermeneutic approach, Muslims can continue to develop a broader and deeper understanding of the teachings of the Qur'an in accordance with the demands of the evolving times.